Tails of the city: caudal autotomy in the tropical lizard, anolis cristatellus, in urban and natural areas of Puerto Rico (2016)
Urbanization creates drastic changes in habitat and presents considerable challenges and new sources of predation to urban-dwelling herpetofauna. Research on lizards has documented increased rates of mortality in urban areas due to generalist predators such as raccoons, feral cats, and domestic animals. Caudal autotomy (self-amputation of the tail) is a defense mechanism used to escape predation in a wide range and large number of lizard species. The tail is autotomized to evade capture, and in most species with autotomy, the tail is regenerated partially or completely. Caudal autotomy can be used as an indirect measure of predation environment; however, few prior studies have used lizard caudal autotomy to measure the predation environment of urban areas. We compared caudal autotomy rates in the Puerto Rican crested anole, Anolis cristatellus, between urban and natural sites in four Puerto Rican municipalities. Across all municipalities, we found the frequency of caudal autotomy and regeneration to be consistently, significantly higher in urban than in natural areas. Our findings suggest that differences exist in the predation regime experienced by lizards in urban and natural habitats across the island of Puerto Rico. At this time, however, we are not able to identify the specific nature of the difference in predation regime between sites. The difference in autotomy rate that we found may be driven by higher predation pressure in urban areas, differences in the predator assemblage between sites, or simply lower predator efficiency in urban habitats.